Probiotic properties and antibacterial activity against aquatic pathogens of non-starch, polysaccharide-degrading Bacillus velezensis newly isolated from termite (Termes comis) guts - Chanworawit, Kittipong; Tomtong, Putsawee; Chuglum, Poramet; Deevong, Pinsurang (Agriculture and Natural Resources, 2025)
Importance of the work: Termite gut bacteria harboring non-starch polysaccharide (NSP) degradation and probiotic properties are beneficial as a microbial fermentation additive for plant-based animal feed. Objectives: To evaluate the probiotic properties and antimicrobial activity against aquatic animal pathogens of NSP-degrading Bacillus sp. isolated from the guts of the termite Termes comis. Materials and Methods: NSP-degrading bacteria were isolated and screened from the guts of termites. The selected bacteria were identified molecularly and assayed for NSP-degrading activity, as well as being evaluated for their antimicrobial ability and probiotic properties (stress tolerance, antioxidant activity, bacterial safety profile and cell surface characteristics). Results: Among the 49 bacterial isolates obtained from the termite gut samples, the isolates Tc10, Tc19 and Tc44 were selected based on the presence of NSP-degrading enzymes (cellulase, pectinase and xylanase). Based on 16S rRNA gene sequence analysis, these three isolates were closely related to Paenibacillus lutimineralis (Tc10), Paenibacillus alvei (Tc19) and Bacillus velezensis (Tc44). Among them, only B. velezensis Tc44 could survive in gastrointestinal tract conditions of pH 2.5 and 0.3% bile salt, exhibiting broad-spectrum inhibition against all five tested aquatic pathogenic bacteria. Furthermore, it had the highest antioxidant activity and presented NSP-degrading enzyme activity against all tested types, as well as being harmless based on hemolytic activity, biogenic amine production and antibiotic susceptibility. In addition, Tc44 had the highest adhesion capability to Caco-2 and HT-29 cells, with anti-adhesion ability against all the tested pathogens, based on competition, inhibition and displacement assays. Main finding: Scientific knowledge was documented of NSP-degrading Bacillus-based probiotics obtained from gut samples of the soil-feeding Termes comis, which could be beneficial for nutritive improvement in animal feed and the prevention of aquatic animal disease in aquaculture.